Osamu Tezuki’s Manga Crime and Punishment: Patterns and Paradoxes of Intermediality - Olga S. Kryukova; Maria B. Rarenko (Достоевский и мировая культура: Филологический журнал, 2024)
The article is dedicated to the analysis of the manga by the classic of Japanese anime Osamu Tezuka, Crime and Punishment, based on the eponymous novel by Fyodor Dostoevsky. It is no coincidence that Dostoevsky’s novel served as the “material” for the creation of manga, since the problems considered in it, primarily moral, are of a universal nature and remain relevant today. The period of the late 20th and early 21st centuries is marked by tremendous changes in nearly all spheres of human existence and this fact has inevitably influenced human consciousness and its attitude toward the ways of cognition. The tendency to “consume” that emerged at the end of the 20th century gave rise to a special type of information acquisition, known as “infotainment” (from the English “information” and “entertainment”), which has become one of the characteristics of modern mass culture. This technique, being hybrid in nature, uses stylistic resources of various discourses. The article shows that, having gone beyond the national framework, manga ceases to be confined to the exclusively Japanese book publishing industry. The analyzed manga was published in Japanese in 1953, becoming a clear example of a “secondary text” (according to A.I. Novikov’s terminology), the purpose of which is to popularize Dostoevsky’s work among Japanese youth. Tezuka, demonstrating a deep knowledge of Russian culture, Fyodor Dostoevsky’s and Lev Tolstoy’s works, uses Disney animation techniques when creating manga, as becomes evident when analyzing the actual visual techniques of creating the image of Raskolnikov. Osamu Tezuka’s Crime and Punishment was translated into Russian in 2012 and has not yet been the subject of special research as an example of intersemiotic translation.